Doubling of the magnetic energy product in ferromagnetic nanowires at ambient temperature by capping their tips with an antiferromagnet. (28th June 2017) - Wang, F Z; Salikhov, R; Spasova, M; Liébana-Viñas, S; Bran, C; Chen, Yu-Shen; Vazquez, M; Farle, M; Wiedwald, U
Abstract: We present an approach to prepare free-standing tips of micrometer-long nanowires electrodeposited in anodic aluminum oxide nanopores. Such open tips can be further processed, e.g. for vertical interconnects of functional layers or for tailoring the magnetization reversal of ferromagnetic nanowires. The magnetic switching of nanowires is usually initiated by vortex or domain formation at the nanowire tips. We show that coating the tips of Fe30 Co70 nanowires (diameter 40 nm, length 16 μ m) with thin antiferromagnetic Fe50 Mn50 capping layers (thickness ≈10 nm) leads to magnetic hardening with a more than doubled energy product at ambient temperature.